Promoting independence for people with disabilities - Jurkovičová, Petra; Špinarová, Gabriela; Vachalová, Veronika; Růžičková, Veronika; Sedláčková, Dagmar (Journal of Exceptional People, 2023)
The following post aims to present partial results from the ongoing research, which is based on the initiative of the Abakus Foundation. The main objective of the project is to map good practice in the system of support for the independence of young adults with disabilities in the Czech Republic. Supporting the independence of people with disabilities is one of the important areas that contributes to improving the quality of life. This concerns both the disabled individual and the person caring for them. In this paper, we will offer a brief insight into the issue of independence and partial results of the research carried out.